Review Psychoanalysis: Dimensions Personality Any Novel Characters Other Than Rain Through Analysis Conflict Inner The main character - Berthin Simega; Milka; Sugino Paundanan (Universitas Islam Negeri Palopo, 2025)
Conflict in the novel Anything but Rain against the psychological background element in the main self-figure main. Research This aim analyze conflict inner figure main in Anything but Novels​ Rain Work Okki Rizka Septiana. Type study qualitative based on observation phenomenon psychological figure story in the novel. Data collected through technique reading and technique note. Data processed with technique Miles & Huberman data analysis and analyzed based on plan Sigmund Freud's psychoanalysis. Research results show that conflict inner feelings experienced by the character main that is Hero in the novel Anything but Rain motivated by past trauma. Friend Hero namely Faiz dies without clear cause and Wira​ accused as the killer. Tragedy the haunt self-Hero, so that often experience imbalance emotions. Guilt, no​ believe self, gloomy, difficult adapt, and not brave take decision, is form from symptom psychological experiences​ Hero. Conflict inner happens Because structure personality figure story that is id, ego, and superego often clash. Id control self-Hero, when avoid past memories​ namely guilt​ to death Faiz moment they compete in taekwondo. This bothers the ego that tries accept condition moment Now namely Hero must focus with the world of taekwondo. Every time he plays taekwondo, he always remembers death Faiz. Superego present for control action id. Hero Finally return mastered his ego and can accept condition after accept advice from Mother Faiz that everyone has​ guilty and should Hero Study forgive self alone. Advice from Mother Faiz is the superego area that is capable of subdue id Hero.